Lexical and cohesive links in EFL learners' writing: Exploring the use of task based language teaching - Albelihi, Hani Hamad M. (Frontiers in Education, 2022)
As English has become the preferred language for recording current innovation and technological breakthroughs, text is the essential medium through which EFL learners enhance their writing abilities. Desirable though it may be, the researcher’s experience has shown that most male students have just rudimentary L2 writing skills and are unable to write coherent passages in English. This implies a chasm between learners’ lexical and cohesive connections and earlier research has focused on ways and means to bridge this gap. However, the current study is ground-breaking in this field as it explores the efficacy of task-oriented training in filling this chasm. Using linguistic learning methods, the current research examines the efficacy of lexical and cohesive links in enhancing undergraduates' writing. The study sample comprises 35 learners from an intermediate EFL reading class who are exposed to an intervention lasting 15 weeks. Data analysis shows that in the post-test, the learners' grammatical and vocabulary skills are enhanced dramatically, particularly in the discourse analysis sections. Furthermore, during group work activities, (i) students are more engaged and motivated, and they acquire more knowledge about the language system, identification, cause and effect, ‘if’ clause and the purpose and function of using the passages given; (ii) half of the students' grammar proficiency and use of lexical items was correct in the writing output. Finally, the study shows that the biggest obstacle that the students faced in their writings and which they struggle to master is the use of the ‘if’ clause which only 13 students could finally master. In addition, the study shows that (73%) of the students could master the discursive linkers in their writings better than the lexical or grammatical elements. Ultimately, the present study offers practical consequences that EFL teachers may want to contemplate including in their future classes.